Pengaruh Penerapan Model Pembelajaran Problem Based Learning Terhadap Kemampuan Pemecahan Masalah Siswa di MTs Muhammadiyah Alamanda - Indah Nurbaiti; Arifmiboy Arifmiboy; Iswantir Iswantir; Afrinaldi Afrinaldi (Simpati, 2023)
The background of the problem in this study is due to the low problem solving ability of students, where in the learning process educators still use the cerama or discussion method so that during learning students only listen and receive explanations of material without any mastery of relevant competencies and structures. The learning process is still using the revised 2013 curriculum, which requires students to be able to have productivity, creativity, innovation and have activities that can be contributed to social life. The purpose of this study was to determine how much “The Effect of Problem Based learning Model Application on students Problem Solving Ability at MTs Muhammadiyah Alamanda Kec. Kinali. Kab. Pasaman Barat”. This quantitative research uses the type of research Quasy Experimental Design. The population in this study amounted to 60 students, namely all seventh grade students at MTs Muhammdiyah Alamanda. The sample used in this study amounted to 60 students, with random sampling technique if the data was normally distributed and homogeny. The data analysis technique used is a description of the research data, normally, homogeny and hypothesis test. The results showed that testing using the t-test obtained the results of thitung = 13.863 and ttable= 1.6715 and the value of Sig. (2-tailed) = 0.000 at the problem based learning model has an influence on students problem solving skills.